ECONOMIC ANALYSIS OF DRIP‐IRRIGATED KINNOW MANDARIN ORCHARD UNDER DEFICIT IRRIGATION AND PARTIAL ROOT ZONE DRYING2. (19th February 2013) - Panigrahi, P.; Sharma, R. K.; Parihar, S. S.; Hasan, M.; Rana, D. S.
ABSTRACT: The profitability of regulated deficit irrigation (RDI), sustained deficit irrigation (SDI), and SDI with partial root zone drying (PRD) strategies was compared to that with full irrigation (FI: 100% crop evapotranspiration) in drip‐irrigated Kinnow mandarin in northern India. RDI was scheduled with two irrigation levels: no irrigation and 50% crop evapotranspiration (ETc.) imposed in the early fruit growth period (EFGP) and final fruit growth period (FFGP) singly and in combination, whereas SDI was scheduled at 50% ETc and 75% ETc with and without the PRD technique. The highest fruit yield was recorded with FI, which was statistically on a par ( p > 0.05) with that with SDI at 50% ETc with PRD (PRD50 ). Economic‐based comparison shows that all the treatments were economically viable since their profitability (net return, INR 137 000–1 300 000 ha ‐1 and benefit–cost ratio, 2.1–14.3) were viable. The net return generated with PRD50 was statistically ( p > 0.05) at par with that generated with FI. However, the benefit–cost ratio and economic water productivity calculated with PRD50 were found to be significantly ( p < 0.05) higher (36 and 87%, respectively) than that with FI. These results lead us to conclude that the PRD50 strategy could be used to improve irrigation water productivity substantially in commercial Kinnow mandarin orchards in sandy loam soil. Copyright © 2013 John Wiley & Sons, Ltd. RÉSUMÉ: La rentabilité de l'irrigation déficitaire réglementée (RDI), de l'irrigation déficitaire durable (SDI) et SDI avec séchage partiel de la zone racine (PRD) ont été comparées à celle de l'irrigation complète (FI: 100% de l'évapotranspiration des cultures), tous modes en goutte à goutte, sous des mandariniers et dans un site situé dans le Kinnow (Nord de l'Inde). RDI a été prévue avec deux niveaux d'irrigation: aucune irrigation et 50 % de l'évapotranspiration (ETc.) en période de croissance précoce des fruits (EFGP) et dernière période de croissance des fruits (FFGP). SDI a été programmée à ETc. 50% et ETc. 75% avec et sans technique PRD. Le rendement le plus élevé a été enregistré avec des fruits FI, ce qui est statistiquement comparable ( p > 0, 05) à celui de SDI à ETc. 50% et PRD 50. La comparaison économique montre que tous les traitements étaient économiquement viables puisque leur rentabilité est avérée (rendement net, INR 137 000–1 300 000 ha ‐1 et ratio coûts–avantages, de 2, 1 à 14, 3). Le rendement net généré avec PRD50 était statistiquement ( p > 0, 05) comparable à celui généré par FI. Toutefois, le ratio avantages‐coûts et la productivité économique de l'eau calculée avec PRD50 sont significativement ( p < 0, 05) plus élevés (36 et 87%, respectivement) par rapport à FI. Ces résultats permettent de conclure que la stratégie PRD50 pourrait être utilisée pour améliorer la productivité de l'eau d'irrigation dans les vergers commerciaux de mandarine du Kinnow en sol de limon sableux. Copyright © 2013 John Wiley & Sons, Ltd.